The effects of urbanization and road development on carnivores in southern California - Alonso, Robert Scott, author; Crooks, Kevin R., advisor; Boydston, Erin E., committee member; Noon, Barry R., committee member; Theobald, Dave M., committee member (Colorado State University. Libraries, 2012)
Habitat destruction and degradation is a serious threat to biodiversity, and urbanization and road development are driving factors in habitat loss. As the human footprint continues to expand, the natural landscape becomes increasingly fragmented and human development can create barriers to wildlife movement and gene flow. Carnivores in particular are sensitive to fragmentation and may be used as model animals for understanding how roads and urbanization can fragment wildlife populations. In this thesis, I investigate the effects of urbanization and road development on carnivores in southern California. Since southern California is one of the most populous areas of the country, coupled with high biodiversity, it is a unique area to study the effects of road development and urbanization on carnivores. In the first chapter, I estimate the density of bobcats in a coastal reserve isolated by urbanization using mark-recapture and mark-resight techniques with camera trap data. The use of camera trap data to estimate carnivore abundance is increasingly common, and to date many such studies have utilized a mark-recapture framework and focused on carnivores with unique pelage patterns. The recent improvement of mark-resight estimators, however, provides an opportunity to estimate the abundance of carnivores without unique pelage patterns. We utilized both the mark-recapture and mark-resight frameworks to estimate bobcat population sizes in a geographically isolated urban reserve in southern California. Due to their sensitivities to urban fragmentation, bobcats have been a focal species in several studies throughout southern California, yet few population estimates exist for this region. Since bobcats are individually identifiable, and a subset of the study population was physically marked with GPS telemetry collars, we were able to compare the utility of both the mark-recapture and mark-resight frameworks for carnivore population estimation with camera trap data. We deployed a sampling grid of 30 cameras throughout the study area and recorded 109 bobcat photos during 4,669 camera nights from July 2006 through January 2007. Density point estimates were reasonably consistent with prior studies and ranged from 0.40 to 0.55 bobcats per km2 depending upon the estimator used, but the confidence intervals for all estimates overlapped suggesting that they were not significantly different. Percent confidence interval length ranged from 150% to 180% indicating a low amount of precision for all of our estimates. We conclude that mark-resight estimators performed comparably to the mark-recapture estimators and show promise for use with camera trap data to estimate carnivore population sizes. The low precision for both our mark-recapture and mark-resight estimators, however, highlights the sensitivity of both frameworks to small datasets typical of large carnivore studies. In future studies, it will be important to develop techniques to increase capture probabilities of target species to maximize the utility of camera traps for estimating population sizes. In the second chapter, I evaluate the effects of a road expansion and mitigation project on underpass usage of three target species: bobcat, coyote and mule deer. Roads can negatively impact wildlife, particularly large mammals. In response, transportation agencies have implemented mitigation measures like the installation of wildlife fencing and wildlife crossing structures. The evaluation of these mitigation measures is crucial to determine the success of reducing road impacts. Herein, we evaluate a road expansion and mitigation project completed by the California Department of Transportation along State Route 71 (CA-71) through the Chino Hills southeast of Los Angeles. We designed a remote camera survey to study how the widening of CA-71 and implementation of mitigation measures affected large mammal movement and underpass use. Based on camera detections, bobcat underpass use was higher in the construction and mitigation zone after construction than before, but there was no difference in use of underpasses in the impact compared to the control zone in either time period. Underpass use by coyotes was higher in the control zone than in the impact zone, but there was no difference in use between the before and after periods. Small numbers of mule deer detections at few underpasses precluded a comparison between the control and impact zones, but a comparison of before and after periods revealed that mule deer underpass use was slightly higher post-construction. We cannot fully attribute increased detections post-construction to mitigation efforts, and other factors, such as habitat availability, urbanization, or demography, may have also influenced underpass use along CA-71. Nonetheless, even with the expansion of the freeway and subsequent increase in traffic volume, mitigation structures along CA-71 did allow for continued movement and hence connectivity across the roadway for the target species.
Keywords: southern California; coyote (Canis latrans); urbanization; bobcat (Lynx rufus); camera trap